2012
DOI: 10.1248/bpb.b12-00121
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein Potently Inhibits Rho Kinase Activity and Suppresses Actin Stress Fiber Formation in Angiotensin II-Stimulated H9c2 Cells

Abstract: Baicalein is a flavonoid (5,6,7-trihydroxy-2-phenyl-4H-1-benzopyran4-one) and an active principle in Scutellaria baicalensis. The present study was performed to investigate the mechanisms underlying the antifibrotic effects of baicalein with a focus on Rho kinase (ROCK) inhibition. The effect of baicalein on ROCK activity was analyzed using an immobilized metal affinity for phosphochemicals (IMAP)-based time-resolved fluorescence resonance energy transfer (TR-FRET) assay. The underlying mechanisms of baicalein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
(28 reference statements)
1
8
0
Order By: Relevance
“…It has been widely used as a therapeutic agent for microbial infection in East Asian countries. Moreover, baicalein possesses many biochemical and pharmacological benefits, including anti-tumor, anti-fibrogenic (Oh et al 2012;Shimizu 2001), anti-inflammatory (Liu et al 2014;Zhang et al 2014), and cardiovascular protective effects. Baicalein has been increasingly used against renal (Wang et al 2012), myocardial (Kong et al 2011), pulmonary (Gao et al 2013), and hepatic (Inoue and Jackson 1999;Shimizu 2000;Sun et al 2010) fibroses as a potential antioxidant.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely used as a therapeutic agent for microbial infection in East Asian countries. Moreover, baicalein possesses many biochemical and pharmacological benefits, including anti-tumor, anti-fibrogenic (Oh et al 2012;Shimizu 2001), anti-inflammatory (Liu et al 2014;Zhang et al 2014), and cardiovascular protective effects. Baicalein has been increasingly used against renal (Wang et al 2012), myocardial (Kong et al 2011), pulmonary (Gao et al 2013), and hepatic (Inoue and Jackson 1999;Shimizu 2000;Sun et al 2010) fibroses as a potential antioxidant.…”
Section: Introductionmentioning
confidence: 99%
“…Fas is one of the most thoroughly evaluated ROCK inhibitors and has been demonstrated to provide a beneficial effect in the management of neurological disorders, including depression, stroke, and Alzheimer’s disease 23,28 . BA is a natural ingredient with promising neuroprotective activity, including antidepressive activity, which has been reported to have potential in inhibiting ROCK activity 29 . Thus we adopted Fas, a ROCK inhibitor, and BA, a natural bioactive ingredient with inhibitory effects on ROCK2, to evaluate the antidepressant effects of ROCK2 inhibition in our present study.…”
Section: Discussionmentioning
confidence: 99%
“…flower (TFR), an effective part of this flower, are comprised of flavones such as hyperin, rutin, quercetin, and other flavonoids [17, 18]. It was reported that some flavonoids have potential antioxidant, anti-inflammatory, and antifibrotic effects, with the latter being elicited through modulation of the cardiac U-II/UTR pathway [19] and inhibition of ROCK activity [20, 21]. Our previous studies found that TFR protects the heart against acute MI injury in rabbits [22] and rats [23], and TFR also has a protective effect on cultured rat cardiomyocytes anoxia/reoxygenation damage via inhibition of ROCK1/2 [24].…”
Section: Introductionmentioning
confidence: 99%